Liberalismo, Justiça Social e Responsabilidade Individual - Alvaro de Vita (Universidade do Estado do Rio de Janeiro, 2011)
The study examines the contemporary normative debate on social justice from the perspective of the normative political theory of "egalitarian liberalism". Contrary to an anti-egalitarian liberal political theory, or "libertarianism", the argument is that a notion of "effective freedom", and not negative freedom, is central to egalitarian liberalism. Additionally, in contrast to a theoretical current of egalitarianism known as "luck egalitarianism", the article further argues that although egalitarian liberalism assigns special importance to individual responsibility, it does so (unlike "luck egalitarianism") without implying any concession to the conservative critique of egalitarianism and the state's redistributive action.